Actividad antimicrobiana de la solución de nanopartícula de plata en cultivo de Enterococcus faecalis - Garcia, Arturo Javier Aranda; Kuga, Milton Carlos [UNESP]; Chávez Andrade, Gisselle Moraima; McGregor, Arturo Cabrera; Rojas-López, Sagrario; Castro Zepeda, Gastón; García, Fernando Antonio Vázquez; Weckwerth, Paulo Henrique; Juárez Broon, Norberto (My University, 2013)
Objective. The objective of this study was to evaluate the antimicrobial activity of the silver nanoparticles solution in enterococcus faecallis cultures (ATCC 29212), compared with various solutions of sodium hypoclorithe (NaOCl). Material and methods. Five Agar Petri plates were inoculated with E. faecallis and each of them was placed a cellulose dish embedded with silver nanoparticles solution, or a solution of sodium hypochlorite evaluated (Viarzon, Cloralex, Clorox). Chlorhexidine digluconate 2% was used as positive control and sterile saline solution was used as negative control. After 24 hours of incubation at 37ºc, under aerobic conditions, the zones of inhibition of bacterial growth were measured and the results subjected to the statistical t test among the experimental groups (= 5%). Results. The Cloralex showed to be the most effective reflected in the extent of inhibition in relation to other substances (p< 0.05), except that the chlorhexidine digluconate 2% (p> 0.05). The solution of silver nanoparticles provided a greater zone of inhibition than the sodium hypochlorite solution (Clorox) and Viarzon (p< 0.05). Clorox and Viarzon didn't provide zones of inhibition and were similar to each other (p> 0.05). Conclusions. The solution of silver nanoparticles presents antimicrobial activity in cultured E. faecallis, even higher than other commercial forms of sodium hypochlorite. Further studies should be carried out to determine its viability as irrigating solution in endodontics (AU)

Objetivo. El objetivo del estudio fue evaluar la actividad antimicrobiana de la solución de nanopartículas de plata en cultivo de Enterococcus faecalis (ATCC 29212) comparándola con diversas soluciones de hipoclorito de sodio (NaOCl). Material y Métodos. Cinco placas de Petri en agar fueron inoculadas con E. faecalis y sobre cada una de ellas se colocó un disco de celulosa saturado de solución de nanopartículas de plata, así como en cada una de las soluciones de hipoclorito de sodio evaluadas (Viarzon, Cloralex, Clorox). El digluconato de clorhexidina al 2% y solución salina estéril fueron utilizados como control. Transcurridas 24 horas de incubación a 37°C, en condiciones de aerobiosis, las zonas de inhibición de crecimiento bacteriano fueron medidas y los resultados sometidos a la prueba ôtö entre los grupos experimentales (= 5%). Resultados. El Cloralex presentó la mayor media de inhibición en comparación con las demás substancias (p < 0,05), excepto con digluconato de clorhexidina al 2% (p > 0,05). La solución de nanopartículas de plata proporcionó mayor zona de inhibición que Clorox y Viarzon (p <0,05). El Clorox y el Viarzon no proporcionaron zonas de inhibición y fueron semejantes entre sí (p > 0,05). Conclusiones. La solución de nanopartículas de plata presenta actividad antimicrobiana en cultivo de E. faecalis, incluso mayor que las formas comerciales de hipoclorito de sodio. Futuros estudios deben ser realizados para comprobar su viabilidad como solución de irrigación en endodoncia (AU)
Antimicrobial activity of silver nanoparticles solution on culture of Enterococcus faecalis